LSP TEACHING TO ADULT LEARNERS: EXPERIENCE OF DEVELOPING LSP COURSE FOR AIRPORT FRONT LINE PERSONNEL - Lutskovskaia, Larisa (PEOPLE: International Journal of Social Sciences, 2016)
The development of the modern world is increasingly characterized by globalization, which affects many social aspects including professional ones and sets new challenges not only to university students but to adult professionals as well. Increasing scientific and business international contacts render foreign language skills (at least English as the language of international communication) a must for highly qualified specialists; thus one of the challenges that adult professionals face is to acquire foreign language skills for effective communication in professional settings. At the same time, LSP teachers face similar challenges of helping adult learners to develop targeted competencies in the shortest term possible. The article focuses on comparing strategies of preparing and structuring teaching materials for students and adult professionals. The article also discusses challenges in developing LSP course for airport front line personnel. The conclusion outlines the main solutions in teaching material selection, it’s structuring and arranging in the course designed for 40 academic hours of total workload, as well as presents practically obtained results of the course approbation in class.